“Love and Self-Love”: The Balance between Sympathy and Self-Respect in Louisa May Alcott’s Early Fiction - Asun López-Varela Azcárate (European Journal of American Studies)
This paper explores one of the early short stories by Louisa May Alcott in order to offer an example of a problem that plagued women in 19th century America, wanting to thrive both in the domestic and in the public spheres. By focusing on “Love and Self-Love,” an early short story, the paper highlights one of the major concerns at the time of the emergence of the first proto-feminist movements: the balance between women’s inclination to sympathy for others and their own self-esteem. The plot revolves around self-respect and stages forms of female empowerment by using fiction as a form of education oriented towards creating awareness in the public sphere.